Increasing steam power plant efficiency through exergy Analysis - حسن, أيوب; حلوم, عفراء (Latakia University Journal -Engineering Sciences Series, 2020)
This study dealt with the exergy analysis of the steam generating station at Banias thermal power plant with nominal capacity 170MW, in order to increase their efficiency. The thermal efficiency results were compared with the exergy efficiency to show that the exergy analysis could be valuable for improving the station performance. We have determined the main resources of losses of energy and exergy in the station. This method provides us with the means and methods that lead to the development of the system performance and reduce the impact of the surrounding medium. A study of station parameters was also completed that show how the performance of the system changes by different factors. Where it was found that the combustion chamber is the main contributor of the exergy destroy followed by the heat exchanger of the boiler system.